The Intrinsic Cardiac Nervous System: From Pathophysiology to Therapeutic Implications - Giuseppe Giannino; Valentina Braia; Carola Griffith Brookles; Federico Giacobbe; Fabrizio D’Ascenzo; Filippo Angelini; Andrea Saglietto; Gaetano Maria De Ferrari; Veronica Dusi (Biology, 2024)
The cardiac autonomic nervous system (CANS) plays a pivotal role in cardiac homeostasis as well as in cardiac pathology. The first level of cardiac autonomic control, the intrinsic cardiac nervous system (ICNS), is located within the epicardial fat pads and is physically organized in ganglionated plexi (GPs). The ICNS system does not only contain parasympathetic cardiac efferent neurons, as long believed, but also afferent neurons and local circuit neurons. Thanks to its high degree of connectivity, combined with neuronal plasticity and memory capacity, the ICNS allows for a beat-to-beat control of all cardiac functions and responses as well as integration with extracardiac and higher centers for longer-term cardiovascular reflexes. The present review provides a detailed overview of the current knowledge of the bidirectional connection between the ICNS and the most studied cardiac pathologies/conditions (myocardial infarction, heart failure, arrhythmias and heart transplant) and the potential therapeutic implications. Indeed, GP modulation with efferent activity inhibition, differently achieved, has been studied for atrial fibrillation and functional bradyarrhythmias, while GP modulation with efferent activity stimulation has been evaluated for myocardial infarction, heart failure and ventricular arrhythmias. Electrical therapy has the unique potential to allow for both kinds of ICNS modulation while preserving the anatomical integrity of the system.